Laser ablation single particle aerosol mass spectrometry for the direct analysis of raw coal samples. Issue 7 (13th April 2018) - Zhu, Hui; Liu, Mei; Guo, Teng; Xu, Li; Dong, Junguo; Feng, Jialiang; Cheng, Ping; Zhou, Zhen
Abstract : LA-SPAMS was developed for online measurement of the size and chemical composition of individual particles ablated from solid materials. Abstract : A new solid material analysis method using laser ablation single particle aerosol mass spectrometry (LA-SPAMS) has been developed. The instrument has been designed to be compact with a high-energy pulse laser system to generate the particles, a closed chamber to settle the samples and also to prevent particle interference from the air, and a single particle aerosol mass spectrometer to measure the aerodynamic size and the chemical composition of the particles precisely and simultaneously. LA-SPAMS focuses on the on-line measurement of the size and chemical composition of individual particles ablated from solid materials and was used to analyze five raw coal samples from different locations in China. In total, more than 100 000 particles were sized ranging from 200 to 2000 nm. Furthermore, around 20–40% of the particles were chemically analyzed to produce both positive and negative mass spectra. The particle size distributions for the five coal samples differ significantly, having peaks of various sizes and different profiles. Mass spectral signatures of the five samples were studied by analyzing the average mass spectrum of each sample and each particle cluster was extracted using the ART-2a method. The main compositions observed in the average mass spectra of the samples include metallic and nonmetallic elements, elemental carbon, organic carbon, and other compounds, and the differences between the samples are the chemical compositions in each group. The particles ablated from the five raw coal samples were divided into nine classes according to their primary chemical composition, and the particle class compositions for the coal samples are very specific allowing them to be used as the particle markers to characterize the coal samples. LA-SPAMS avoids tedious and time-consuming chemical digestion processes, allows the direct analysis of solid materials and the simultaneous determination of all detectable components based on single particle analysis, and realizes real-time online analysis. It is particularly suited to the analysis of heterogeneous materials such as coals and mineral ores and has applications in fields such as geology and metallurgy.